Multicenter nellix endovascular aneurysm sealing system experience in aneurysm sac sealing - Böckler, Dittmar (Journal of vascular surgery, 2015)
Objective Despite improvements in endograft devices, operator technique, and patient selection, endovascular repair has not achieved the long-term durability of open surgical aneurysm repair. Persistent or recurrent aneurysm sac flow from failed proximal sealing, component failure, or branch vessel flow underpins a significant rate of reintervention after endovascular repair. The Nellix device (Endologix, Irvine, Calif) employs a unique design with deployment of polymer-filled EndoBags surrounding the endograft flow lumens, sealing the aneurysm sac space and potentially reducing complications from persistent sac flow. This retrospective analysis represents the initial experience in consecutive patients treated with the device in real-world practice. Methods This study was performed at six clinical centers in Europe and one in New Zealand during the initial period after commercialization of the Nellix device. Patients underwent evaluation with computed tomography and other imaging modalities following local standards of care. Patients were selected for treatment with Nellix and treated by each institution according to its endovascular repair protocol. Clinical and imaging end points included technical success (successful device deployment and absence of any endoleak at completion angiography), freedom from all-cause and aneurysm-related mortality, endoleak by type, limb occlusion, aneurysm rupture, and reintervention. Results During a 17-month period, 171 patients with abdominal aortic aneurysms were treated with the Nellix device and observed for a median of 5 months (range, 0-14 months). The 153 male and 18 female patients with mean age of 74 ± 7 years had aneurysms 61 ± 9 mm in diameter with an average infrarenal neck length of 28 ± 15 mm and infrarenal angulation of 37 ± 22 degrees. Technical success was achieved in all but two patients (99%); one patient had a type Ib endoleak and another had a type II endoleak. Through the last available follow-up, type Ia endoleak was observed in five patients (3%), type Ib endoleak in four patients (2%), and type II endoleak in four patients (2%). There were eight limb occlusions (5%), among which seven were evident at the 1-month follow-up visit. Aneurysm-related reinterventions were performed in 15 patients (9%). There were no aneurysm ruptures or open surgical conversions. Conclusions this first multicenter postmarket report of the Nellix device for infrarenal abdominal aortic aneurysm repair demonstrates satisfactory results during the initial learning phase of this new technology. The rate of aneurysm exclusion was high, and frequency of complications was low. More definitive conclusions on the value of this novel device await the results of the ongoing Nellix EVAS FORWARD Global Registry and the EVAS FORWARD investigational device exemption trial.
Gesehen am 21.02.2017